Exploring Gender Differences in the Role of Trait Preferences among Stakeholders in the Rice Value Chain in Ghana - Frimpong, B.N.; Asante, M.D.; Prah, S.; Ayeh, S.J.; Sakyiamah, B.; Zenna, Negussie; Mujawamariya, Gaudiose; Tufan, Hale Ann (MDPI, 2023)
This paper examines the gendered trait preferences for rice and their role in the adoption of improved rice varieties among men and women rice farmers in Ghana. Four hundred rice farm households and 261 consumers were surveyed across 20 communities using a simple random sampling technique. Kendall’s coefficient of concordance, Tobit, and the multivariate probit regressions were used in the analyses. The results show differences in preferences for cooking quality traits and postharvest traits among men and women farmers. There was also a gender differential in the intensity of purchasing rice among men and women consumers. The results show that rice farmers’ decisions to adopt any of the four varieties—AGRA rice, Jasmine, Togo Marshall, or Amankwatia—are influenced by age, being married or indigenous, years of schooling, off-farm activities, farming experience, household size, farm size, FBO membership, extension contact, market proximity, and access to credit. To improve the rice value chain in Ghana, rice breeding efforts should consider varieties with trait preferences such as being tolerant of pest and diseases, aromatic, early maturing, and tolerance to shattering. However, to enhance the consumption of improved rice varieties, breeding efforts should target varieties that are aromatic, good textured, and have medium-sized grains for female consumers, while for male consumers preferred varieties would be less easily broken, white grain color, translucent, and with short cooking time.